2016
DOI: 10.3109/09546634.2016.1163317
|View full text |Cite
|
Sign up to set email alerts
|

Topical calcineurin inhibitors in eczema and cancer association: A cohort study

Abstract: In this first Asian study on the risk of TCIs and malignancies, we do not find an association between use of tacrolimus and pimecrolimus in atopic and endogenous eczema and the overall development of malignancies. However, the use of topical tacrolimus was found to be associated with the development of B-cell acute lymphoid leukemia in pediatric eczema patients; further studies are required to investigate if a true association indeed occurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 35 publications
2
28
0
2
Order By: Relevance
“…When compared to topical corticosteroids, calcineurin inhibitors tend to elicit more adverse events such as burning or pruritus [39-41]. Additionally, studies have linked calcineurin inhibitors to malignancies such as leukemia and lymphoma [42, 43]. Given that past research indicates a correlation between industry funding and pro-industry results [44], these findings raise the question as to whether the obscuring of adverse events is intentional from an industry perspective.…”
Section: Discussionmentioning
confidence: 99%
“…When compared to topical corticosteroids, calcineurin inhibitors tend to elicit more adverse events such as burning or pruritus [39-41]. Additionally, studies have linked calcineurin inhibitors to malignancies such as leukemia and lymphoma [42, 43]. Given that past research indicates a correlation between industry funding and pro-industry results [44], these findings raise the question as to whether the obscuring of adverse events is intentional from an industry perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Use of calcineurin inhibitors in paediatric patients for prolonged periods of time should be monitored carefully. Although the evidence available is insufficient to suggest causality, the Pediatric Advisory Committee for the Food and Drug Administration has retained a 'black box' warning for use in the United States, citing a potential risk of B cell leukaemia with the use of calcineurin inhibitors in paediatric patients (72,73).…”
Section: Topical Immunomodulatorsmentioning
confidence: 99%
“…Pimecrolimus is not available for use in Japan b Children aged C 2 years and adolescents aged \ 16 years c Adolescents aged C 16 years and adults found evidence of increased cancer risk [59,60]. Indeed, the first Asian study to investigate the risk of malignancies with TCI in patients with AD found no association between pimecrolimus and tacrolimus use and overall development of malignancies [61]. Furthermore, a recent prospective, observational study of approximately 8000 children with AD who were treated with tacrolimus ointment for C 6 weeks observed no incidence of lymphoma over a 10-year period [62].…”
Section: Anti-inflammatory Treatmentmentioning
confidence: 99%